Surabaya di persimpangan tradisi dan modernitas: Menjaga warisan di tengah kemajuan - Nadhiroh, Tahta Alfi (Maliki Interdisciplinary Journal, 2025)
As the second-largest metropolitan city in Indonesia and the economic hub of East Java, Surabaya faces a unique challenge in maintaining a balance between tradition and modernity. This article explores how these two aspects coexist in Surabaya, highlighting the preservation of cultural heritage, such as traditional performances, iconic cuisine, and historical sites. On the other hand, modernization brings advanced infrastructure and rapidly evolving technology, impacting the lifestyle of its residents and presenting new challenges for cultural preservation. This article emphasizes the collaborative efforts of various parties in maintaining cultural identity amidst global dynamics, making Surabaya an example of a city that harmoniously blends tradition and progress.